Left Ventricular Myocardial Function in Children With Pulmonary Hypertension. (August 2015) - Burkett, Dale A.; Slorach, Cameron; Patel, Sonali S.; Redington, Andrew N.; Ivy, D. Dunbar; Mertens, Luc; Younoszai, Adel K.; Friedberg, Mark K.
<x xml:space="preserve">Abstract</x> Background— Through ventricular interdependence, pulmonary hypertension (PH) induces left ventricular (LV) dysfunction. We hypothesized that LV strain/strain rate, surrogate measures of myocardial contractility, are reduced in pediatric PH and relate to invasive hemodynamics, right ventricular strain, and functional measures of PH. Methods and Results— At 2 institutions, echocardiography was prospectively performed in 54 pediatric PH patients during cardiac catheterization, and in 54 matched controls. Patients with PH had reduced LV global longitudinal strain (LS; −18.8 [−17.3 to −20.4]% versus −20.2 [−19.0 to −20.9]%; P=0.0046) predominantly because of reduced basal (−12.9 [−10.8 to −16.3]% versus −17.9 [−14.5 to −20.7]%; P<0.0001) and mid (−17.5 [−15.5 to −19.0]% versus −21.1 [−19.1 to −23.0]%; P<0.0001) septal strain. Basal global circumferential strain was reduced (−18.7 [−15.7 to −22.1]% versus −20.6 [−19.0 to −22.5]%; P=0.0098), as were septal and free-wall segments. Mid circumferential strain was reduced within the free-wall. Strain rates were reduced in similar patterns. Basal septum LS, the combined average LS of basal and mid interventricular septal segments, correlated strongly with degree of PH (r=0.66; P<0.0001), pulmonary vascular resistance (r=0.60; P<0.0001), and right ventricular free-wall LS (r=0.64; P<0.0001). Brain natriuretic peptide levels correlated moderately with septal LS (r=0.48; P=0.0038). PH functional class correlated moderately with LV free-wall LS (r=−0.48; P=0.0051). The septum, shared between ventricles and affected by septal shift, was the most affected LV region in PH. Conclusions— Pediatric PH patients demonstrate reduced LV strain/strain rate, predominantly within the septum, with relationships to invasive hemodynamics, right ventricular strain, and functional PH measures.